The Role of AI At Pesantren Raudlatul Ulum For Elt Students: Tools Apps, Benefit, and Challenges - Uswatun Ni'mah; Ahmad Mahfudillah (International Journal on Advanced Science, Education, and Religion, 2026)
This research examines the use of Artificial Intelligence (AI) in English language learning among pesantren students, emphasizing its benefits, challenges, and alignment with the educational and moral values of Islamic boarding schools. Unlike previous studies that focused mainly on students living at home or in formal educational settings, this research explores how AI functions in the pesantren environment, where students balance religious studies and face limited access to digital technology. Using an explanatory mixed-methods approach, data were collected through questionnaires to analyze students’ perceptions and followed by interviews to obtain deeper insights. The findings reveal that AI-assisted tools can significantly enhance pronunciation, vocabulary mastery, grammar accuracy, and cultural understanding through interactive learning, instant feedback, and personalized content. Nevertheless, several challenges arise, including students’ busy religious schedules, restricted internet access, lack of digital literacy, and a preference for traditional face-to-face instruction. These factors influence the extent to which AI can be effectively implemented. The study concludes that AI should serve as a supportive learning aid rather than a substitute for teachers. A balanced integration that combines modern technology with traditional teaching approaches is essential. Ultimately, the findings provide valuable implications for improving English learning in Islamic boarding schools while maintaining their distinctive educational character.